Clowning tops hip hop: reflections on teaching at a First Nations school - Davis, Susan (2015)
This project, which is informed by narrative inquiry, examines one teacher’s experiences as she navigated pedagogical challenges of teaching storytelling and hip hop in a First Nations school. The combination of changing educational contexts: shifting from teaching adults to teaching Indigenous youth had a significant outcome on the teacher’s initial attempts to move through the anticipated curriculum. A critical examination of the literature regarding teaching storytelling and hip hop across cultural boundaries, combined with personal journaling of her emergent teaching experiences, led the teacher to an effective and highly successful method of supporting learning through exploring clown and play, among other factors, to achieve enhanced relationships with her students. The project concludes with a description of considerations of personal, contextual, and theoretical factors which impacted her practice and the students’ experiences as well as recommendations for teachers beginning to work with First Nations students or other minority groups. Graduate